Randomized controlled trial of atorvastatin in mild to moderate Alzheimer disease: LEADe - Feldman, H H; Doody, R S; Kivipelto, M; Sparks, D L; Waters, D D; Jones, R W; Schwam, E; Schindler, R; Hey-Hadavi, J; DeMicco, D A; Breazna, A (Neurology, 2010)
There is some evidence that statins may have a protective and symptomatic benefit in Alzheimer disease (AD). The LEADe study is a randomized controlled trial (RCT) evaluating the efficacy and safety of atorvastatin in patients with mild to moderate AD. This was an international, multicenter, double-blind, randomized, parallel-group study. Subjects had mild to moderate probable AD (Mini-Mental State Examination score 13-25), were aged 50-90 years, and were taking donepezil 10 mg daily for > or 3 months prior to screening. Entry low-density lipoprotein cholesterol levels (LDL-C) were > 95 and < 195 mg/dL. Patients were randomized to atorvastatin 80 mg/day or placebo for 72 weeks followed by a double-blind, 8-week atorvastatin withdrawal phase. Coprimary endpoints were changes in cognition (Alzheimer's Disease Assessment Scale-Cognitive Subscale [ADAS-Cog]) and global function (Alzheimer's Disease Cooperative Study Clinical Global Impression of Change [ADCS-CGIC]) at 72 weeks. A total of 640 patients were randomized in the study. There were no significant differences in the coprimary endpoints of ADAS-cog or ADCS-CGIC or the secondary endpoints. Atorvastatin was generally well-tolerated. In this large-scale randomized controlled trial evaluating statin therapy as a treatment for mild to moderate Alzheimer disease, atorvastatin was not associated with significant clinical benefit over 72 weeks. This treatment was generally well-tolerated without unexpected adverse events. This study provides Class II evidence that intensive lipid lowering with atorvastatin 80 mg/day in patients with mild to moderate probable Alzheimer disease (aged 50-90), taking donepezil, with low-density lipoprotein cholesterol levels between 95 and 195 mg/dL over 72 weeks does not benefit cognition (as measured by Alzheimer's Disease Assessment Scale-Cognitive Subscale) (p = 0.26) or global function (as measured by Alzheimer's Disease Cooperative Study Clinical Global Impression of Change) (p = 0.73) compared with placebo.